ANALYSIS OF ECONOMIC GROWTH AND EMPLOYMENT IN CENTRAL JAVA PROVINCE PERIODE 2019-2022 - Mellyana Safitri; Didit Welly Udjianto (International Journal of Multidisciplinary Research and Literature, 2023)
Looking at the current conditions in Central Java, both in the form of potential and opportunities that can be created, especially at the district/city level in the ability to absorb labor. The author of this study aims to determine the potential for labor absorption at the district/city level in Central Java Province and the relationship between economic growth and absorption of labor in Central Java Province. This study examines the impact of Gross Regional Domestic Product and District/City Minimum Wage on Indonesia's Total Labour Force from 2019 to 2022. This study utilizes the effects of Gross Regional Domestic Product and District/City Minimum Wage as independent variables. At the same time, the dependent variable is the Total Labor Force. The data analysis method uses descriptive quantitative with 35 sample observations. The Gross Regional Domestic Product outcomes have a negative and insignificant effect, and the District / City Minimum Wage results also have a negative and little impact